Anarchism, 1914-18 : internationalism, anti-militarism and war - Adams, Matthew S., 1984-; Kinna, Ruth (Manchester University Press, 2017)
A volume that focuses on the complex and multifaceted answers that the international anarchist movement gave to the outbreak of the First World War and its aftermaths and, in turn, the impact of the Great War on the anarchist movement.